Mechanisms of action of fluoride for caries control - Buzalaf, Marília Afonso Rabelo; Pessan, Juliano Pelim [UNESP]; Honório, Heitor Marques; Ten Cate, Jacob Martien (Karger Publishers, 2011)
Fluoride was introduced into dentistry over 70 years ago, and it is now recognized as the main factor responsible for the dramatic decline in caries prevalence that has been observed worldwide. However, excessive fluoride intake during the period of tooth development can cause dental fluorosis. In order that the maximum benefits of fluoride for caries control can be achieved with the minimum risk of side effects, it is necessary to have a profound understanding of the mechanisms by which fluoride promotes caries control. In the 1980s, it was established that fluoride controls caries mainly through its topical effect. Fluoride present in low, sustained concentrations (sub-ppm range) in the oral fluids during an acidic challenge is able to absorb to the surface of the apatite crystals, inhibiting demineralization. When the pH is re-established, traces of fluoride in solution will make it highly supersaturated with respect to fluorhydroxyapatite, which will speed up the process of remineralization. The mineral formed under the nucleating action of the partially dissolved minerals will then preferentially include fluoride and exclude carbonate, rendering the enamel more resistant to future acidic challenges. Topical fluoride can also provide antimicrobial action. Fluoride concentrations as found in dental plaque have biological activity on critical virulence factors of S. mutans in vitro, such as acid production and glucan synthesis, but the in vivo implications of this are still not clear. Evidence also supports fluoride's systemic mechanism of caries inhibition in pit and fissure surfaces of permanent first molars when it is incorporated into these teeth pre-eruptively. © 2011 S. Karger AG, Basel.
Keywords: anticaries agent; antiinfective agent; fluoride; fluorohydroxyapatite; hydroxyapatite; absorption; dental care; dental caries; enamel; human; metabolism; pH; saliva; Absorption; Anti-Bacterial Agents; Cariostatic Agents; Dental Caries; Dental Enamel; Fluorides; Humans; Hydrogen-Ion Concentration; Hydroxyapatites; Saliva; Tooth Remineralization